Overview of in vivo and ex vivo endpoints in murine food allergy models: Suitable for evaluation of the sensitizing capacity of novel proteins? - Castan, Laure; Bøgh, Katrine L; Maryniak, Natalia Z; Epstein, Michelle M; Kazemi, Sahar; O'Mahony, Liam; Bodinier, Marie; Smit, Joost J; van Bilsen, Jolanda H M; Blanchard, Carine; Głogowski, Robert; Kozáková, Hana; et al. (Allergy, 2020)
Significant efforts are necessary to introduce new dietary protein sources to feed a growing world population while maintaining food supply chain sustainability. Such a sustainable protein transition includes the use of highly modified proteins from side streams or the introduction of new protein sources that may lead to increased clinically relevant allergic sensitization. With food allergy being a major health problem of increasing concern, understanding the potential allergenicity of new or modified proteins is crucial to ensure public health protection. The best predictive risk assessment methods currently relied on are in vivo models, making the choice of endpoint parameters a key element in evaluating the sensitizing capacity of novel proteins. Here, we provide a comprehensive overview of the most frequently used in vivo and ex vivo endpoints in murine food allergy models, addressing their strengths and limitations for assessing sensitization risks. For optimal laboratory-to-laboratory reproducibility and reliable use of predictive tests for protein risk assessment, it is important that researchers maintain and apply the same relevant parameters and procedures. Thus, there is an urgent need for a consensus on key food allergy parameters to be applied in future food allergy research in synergy between both knowledge institutes and clinicians.
Keywords: T-Lymphocytes; imunoglobulin G; Body Temperature; Animals; food allergy; Phenotype; Mice; inbrední kmeny myší; modely nemocí na zvířatech; Immunoglobulin G; Cytokines; Mice, Inbred Strains; imunoglobulin E; biomarkers; zvířata; tělesná teplota; cytokiny; potravinová alergie; prevention; animal models; Immunoglobulin E; T-lymfocyty; fenotyp; Disease Models, Animal; Food Hypersensitivity; myši